Isogénie entre courbes elliptiques - Dewaghe L. (Utilitas Mathematica, 1999)
With an equation of an elliptic curve E over a field K, we can give, for a finite subgroup G of E, the equations of the isogenous curve E/G and of the isogeny I : E → E/G and of, in certains cases, the dual isogeny Î.